Analysis of Employees of Outsourcing Companies Using SWAT (Subjective Workload Assessment Technique) and CVL (Cardiovascular Load) Methods - Nuzulatur Rahmah; Akmal Suryadi (Budapest International Research and Critics University, 2022)
A company certainly has an important role for employees in it, this role can determine the success or failure of a company. However, behind the important role of employees, there are also several obstacles, such as the workload of employees. Workload is the difference between a worker's abilities and job requirements. Someone will definitely feel a small, medium and large workload when carrying out activities in a company. Activities carried out by a person can be divided into two categories, namely physical activities and spiritual activities. These two things cannot be separated from each other, but can be distinguished by looking at the dominant activity. In conclusion, this study focuses on the workload experienced by employees of Outsourcing Companies. The purpose of this study is to analyze the workload of each employee at the Outsourcing Company and provide recommendations for corrective actions needed based on the measurement of workload, this study also uses two methods including the SWAT method and the CVL method. includes time 49.91%, effort 23.56%, and stress 26.56%, so that the dimension that has the greatest influence on the workload of employees is the dimension of time. Meanwhile, the CVL method revealed that the 15 employees who felt the highest workload were 31.304%. This research resulted in several suggestions for improvement, namely adding new employees and providing nutritious snacks for employees.